1-(2-Hydroxy-2-phenylethyl)-3-(4-methoxyphenyl)urea - Chang Keun Sung; Sung Kwon Kang; Sung Chun Lee; Yong Suk Shim; Hyeong Choi (Acta Crystallographica Section E, 2011)
In the title compound, C16H18N2O3, the dihedral angle between the 4-methoxyphenyl ring and the urea group is 35.6 (2) °. The H atoms of the urea NH groups are positioned syn to each other. In the crystal, intermolecular N—H...O and O—H...O hydrogen bonds link the molecules into a two-dimensional array in the ac plane; the carbonyl-O atom is trifurcated.